Sosiokultural Perladangan Tradisional Masyarakat Dayak Kalimantan Tengah: Sociocultural Traditional Cultivation of the Dayak People of Central Kalimantan - Sriyana, Sriyana; Husein, Arya Ramadhan Al; Arianti, Silvia (Anterior Jurnal, 2025)
The Dayak farming system in Central Kalimantan is not just an agricultural activity, but also part of a socio-cultural system that is passed down from generation to generation. This practice reflects a harmonious relationship between humans and nature and has strong economic, social, and cultural values. This study aims to analyze farming as a socio-cultural system, explain the challenges faced by the Dayak community in maintaining this practice, and identify the adaptation strategies they carry out to survive in changing conditions. This study uses a qualitative approach with ethnographic methods, involving participatory observation and in-depth interviews with farming communities, traditional leaders, and village officials, as well as documentation studies from various sources related to agrarian and environmental policies. The results of the study indicate that the Dayak farming system socio-culturally functions not only as a livelihood but also as a symbol of cultural identity. Customary rituals, the cooperation system (handep), and belief in forest guardian spirits are still an integral part of farming practices. However, traditional farming practices face major challenges, such as the prohibition of land burning, land conversion to oil palm plantations, and the decreasing interest of the younger generation in farming. To survive, the Dayak community has developed various adaptation strategies, such as modification of farming techniques, livelihood diversification, legal resistance and land rights advocacy, and strengthening communities and social networks.